66 BRAIN HEALTH CLINIC: DEVELOPING INNOVATIVE OPPORTUNITIES TO INTERVENE IN MODIFIABLE VASCULAR RISK FACTORS (VRF) TO IMPROVE COGNITIVE AGEING. (18th November 2021) - Dookhy, J; Hale, C M C; Dolphin, H; Dukelow, T; Fallon, A; Kennelly, S P
Abstract: Background: It is now well established that VRF place immense burden on cognition, including white matter changes, decreased cerebral perfusion and neuro-inflammation. An innovative Brain Health Clinic (BHC) was developed aligned to a specialist memory service to educate people at risk of or living with mild cognitive symptoms, about positive brain health and subsequently design a 'Personalised Prevention Plan' to optimise cognitive ageing. The aim of this study is to report the opportunities identified and addressed to mitigate vascular risk-related cognitive decline in people attending the Brain Health Clinic. Methods: Modifiable VRF (including HbA1c, cholesterol, Body Mass Index (BMI), smoking, alcohol intake and hypertension) were examined in people who attended the BHC between October 2019 and July 2021. In addition to VRFs, sleep, physical activity, sensory, social, and psychological measures are measured and reported to individuals. The VRF values were examined based on current guidelines from the European Society of Cardiology (2018). Results: Forty-five people (mean age 72.6 years, 62.2% females) were included. The average number of modifiable VRF's per person was 3, and a total of 119 VRF's were identified overall. One patient had six modifiable VRF's identified, and 2/45 had none. The most common VRF was elevated BMI present in 33/45 (73.3%). 12/45 (27%) patients were ex-smokers, while 5/45 (11%) still smoked. 5/45 (11%) consumed excess alcohol. 15/45 (33.3%) had elevated cholesterol. 29/45 (64.4%) had elevated systolic blood pressure. Of these, 10/45 (22.2%) were known but poorly-controlled and 19/45 (42.2%) were identified de novo. Similarly, only 1/45 (2.2%) had known diabetes but poorly-controlled, while 9/45 (20.0%) had impaired glucose tolerance identified de novo. Conclusion: The BHC aligned to a memory service provides an opportunity to identify modifiable VRF for declining cognition, and supports people in addressing these by sign-posting to relevant services.